Pandangan Hak Asasi Manusia terhadap Tindakan Tembak di Tempat Oleh Polisi Tanpa Ada Putusan Pengadilan yang Berkekuatan Hukum Tetap - Sherly Budiono; Rasji Rasji (Syntax Literate, 2023)
This study aims to analyze the action of shooting on the spot by the police without a court decision that has permanent legal force based on Law Number 39 of 1999 concerning Human Rights. The method in this study is legal research is a scientific endeavor that aims to examine certain legal phenomena through analysis. The data used in this study are primary data and data. Based on the results of the research, Analysis of Shooting on the Spot by the Police Without a Court Decision with Permanent Legal Force Based on Law Number 39 of 1999 concerning Human Rights it can be concluded that it is the police who are supposed to provide protection, shelter to the community, and be the frontline for enforcement Human Rights, in fact committing gross human rights violations by abusing the authority over firearms without a legally binding court decision but still not paying attention to the applicable Police code of ethics, as well as the charges given by the Public Prosecutor which are not in accordance with the Articles that should apply, namely Article 338 of the Criminal Code regarding